Transcriptional regulator XtgS is involved in iron transition and attenuates the virulence of Streptococcus agalactiae. (September 2021) - Liu, Guangjin; Gao, Tingting; Yao, Huochun; Liu, Yongjie; Lu, Chengping
Abstract: Streptococcus agalactiae (GBS) is an important pathogen that has increasingly received attention for its role in invasive infections and its broad host range. Research on the regulation of gene expression could illuminate GBS pathogenesis. We previously identified a novel transcriptional regulator XtgS, which is a negative regulator of GBS pathogenicity. Here, we demonstrate that XtgS overexpression significantly attenuated GBS virulence in zebrafish infection tests, and XtgS indirectly downregulated the transcription of two iron transport systems based on the results of transcriptomic analysis, electrophoretic mobility shift assays (EMSAs) and lacZ fusion assays. Subsequent studies verified that the inactivation of iron transport system 1 resulted in GBS excessive iron accumulation and attenuated virulence. Thus, we infer that the downregulation of iron transport system 1 caused by XtgS overexpression probably attenuates bacterial virulence, which partially clarifies the mechanism by which XtgS alleviates the pathogenesis. These findings provide new insights into the relationship between exogenous transcriptional regulation and bacterial virulence. Highlights: The regulator XtgS overexpression significantly attenuated GBS virulence. XtgS indirectly downregulated the transcription of two iron transport systems. The inactivation of iron transport system 1 resulted in excessive iron accumulation and attenuated virulence.